Improving Physical Performance and Fall Risk in the Elderly Through Structured Tai Chi: A Quasi-Experimental Investigation in an Indonesian Nursing Home - Silaswati, Shinta; Savitri Pardede, Bella; Jamaludin, Jamaludin; Sutanto, Jusuf (PT. Nursing Genius Care, 2026)
Background: Falls are a major cause of injury and disability among older adults. Tai Chi, with its slow and controlled movements, is a promising intervention for improving balance and reducing fall risk. Purpose: This study evaluated the effect of a structured two-week Tai Chi program on physical performance and fall risk among elderly nursing home residents in East Jakarta, Indonesia. Methods: A quasi-experimental one-group pre-post design was used with 20 participants (mean age 66.4±4.2 years; 85% female). Fall risk was assessed using the Short Physical Performance Battery (SPPB) before and after a 10-session Tai Chi program. Data were analyzed using the Wilcoxon signed-rank test. Results: Pre-intervention SPPB scores indicated high fall risk (Mean=7.8±1.1). Post-intervention scores improved significantly (Mean=9.6±1.0; p=0.046). The proportion of participants classified as